Participation of Russian Workers in Continuing Professional Education - Anastasiya Karavay (Вопросы образования, 2016)
In this paper, we analyze the rates of participation of Russian workers in continuing professional education (CPE) using Rosstat data and sociological surveys, including the 2014 and 2015 Eurobarometer in Russia. We reveal considerable differences in the percentages of workers covered by CPE across age cohorts, personnel categories, and especially industries. Our analysis shows that formalized CPE norms and standards in such industries as education and healthcare have a largely positive effect on the incidence of employee participation in advanced trainings. Next, we demonstrate that the data collection methods used by Rosstat do not allow for a comprehensive analysis of CPE participation rates in all industries, as only large and medium-sized companies are covered by the official statistics, while small businesses, which form the best part of the retail sector, are left out. Besides, the rigid regulatory framework of the official statistics makes it impossible to embrace the diversity of existing types and forms of CPE. There is no single method to measure the rate of participation in continuing education (not only professional), which we demonstrate in our review of methodologies used by Russian and foreign researchers. As a result, comparing the rates of participation in lifelong learning (including CPE) in different countries becomes a challenging task.